2019
DOI: 10.1177/1178646919855940
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide and Demographic and Disease transitions: Moderation is Best

Abstract: Good health and rapid progress depend on an optimal dose of nicotinamide. Too little meat triggers the neurodegenerative condition pellagra and tolerance of symbionts such as tuberculosis (TB), risking dysbioses and impaired resistance to acute infections. Nicotinamide deficiency is an overlooked diagnosis in poor cereal-dependant economies masquerading as ‘environmental enteropathy’ or physical and cognitive stunting. Too much meat (and supplements) may precipitate immune intolerance and autoimmune and allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 331 publications
(268 reference statements)
0
5
0
Order By: Relevance
“…It worth mentioning that nicotinamide hypervitaminosis toxicity state is common if the dose is not maintained. 98 Therefore, in an attempt to decrease the doses of both ascorbic acid and nicotinamide, they were formulated in chitosan nanoparticles in the current study, to a dose up to 10 times less than that of the conventional dissolved powder dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It worth mentioning that nicotinamide hypervitaminosis toxicity state is common if the dose is not maintained. 98 Therefore, in an attempt to decrease the doses of both ascorbic acid and nicotinamide, they were formulated in chitosan nanoparticles in the current study, to a dose up to 10 times less than that of the conventional dissolved powder dose.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, treatment with nicotinamide could be favorable to reduce cell death. , It was previously reported that administration of nicotinamide elevated brain tissue ATP concentrations and attenuated the ATP depletion as well as 5-HT and dopamine depletion, reduced the MDA and nitrite levels, and increased GSH, thus reversing the neurodegenerative effects of several neurotoxins such as amphetamines, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), and 3-nitropropionic acid (3- NP). Unfortunately, the body could absorb a limited amount of nicotinamide at a time, hence requiring the administration of multiple daily doses, which could cause neurotoxicity instead of neuroprotective actions if administered at high doses. It worth mentioning that nicotinamide hypervitaminosis toxicity state is common if the dose is not maintained …”
Section: Discussionmentioning
confidence: 99%
“…"Meat transitions" appear to lead to a reduction in many infections and almost simultaneously (as in the late 19th C UK), trigger a demographic and epidemiological switch toward infertility and auto-immune, allergic and other diseases of modernity. Immune intolerance with changes in T cell subset ratios result from inhibition of Indoleamine 2,3-dioxygenase (IDO) and the tryptophan to kynurenine "immune tolerance" pathway as no longer necessary to supply nicotinamide [60,61]. This immune tolerance extends to the foetus, where it was originally discovered, so may be partly responsible for declines (and occasional reversals), in fertility with modernity -higher doses also affecting cognition and educational levels contributing to a non-coercive form of population control even if not always welcome [25,[62][63][64][65][66][67].…”
Section: Acute Infections and Switch To Auto-immunitymentioning
confidence: 99%
“…Inequality: The Dangers of Meat Haves and Have-Nots in a Nicotinamide-Adenine-Dinucleotide… DOI: http://dx.doi.org/10.5772/intechopen.96748 quantity piece of a complex jig-saw [193][194][195]. Formulae such as Environmental impact = Population x Energy consumed per capita -show that population counts particularly when energy consumed per person is high [196,197].…”
Section: Population Matters Redux -Crunch-time For Non-coercive Measuresmentioning
confidence: 99%